Impacts of Enzymatic Modifications of Legume’s [i.e., Chickpea (Cicer arietinum) and Lentil (Lens culinaris)] Protein Extracts on Pasta Functional Characteristics" - Saleh, Mohammed; Ghanem, Rania; Lee, YoungSeung (Jordan Journal of Agricultural Sciences, 2023)
This study investigated the effect of enzymatic hydrolysis of chickpea and lentil protein extracts on pasta functional characteristics. Wheat flour was substituted with 0, 5, 10, 15,and 20% of hydrolyzed protein extract and non-hydrolyzed extracts from lentils and chickpea flours. Study treatment includes sequential enzymatic followed by acid and then alkaline treatments. Enzymatic hydrolysis of legume protein extracts had significant impacts on legume functional characteristics increase in legume protein hydrolysis resulted in a linear increase in water absorption regardless of enzymatic hydrolysis and/or chemical extraction method. Results showed a decrease in water absorption with protein hydrolysis while enzymatic hydrolysis before protein extraction treatment resulted in the greatest water absorption among treatments. Additionally, chickpea and lentil treatments impacted the treated farinograph resulting in faster arrival time with the enzymatic modification. For instance, arrival time decreased from 138 to 318% for lentils and from 123 to 183% for chickpea indicating a faster dough developing time that would contribute to saving in pasta processing time. Cooking loss of pasta during cooking decreased from 2.5% in the control treatment to 1.2% (i.e., 208% reduction) in the acid, alkaline treated chickpea and to 0.4% (i.e., 625% reduction) in treated lentil samples. The use of Papain (EC 3.4.22.2) enzymatic treatment was the most effective in decreasing the cooking loss of cooked pasta. Cooked pasta hardness also decreased from 2010.6 N in the control sample to 97.7, 39.9 and111.7 N for acidic, sequential acid then for the alkaline treatment of chickpea, respectively. Similar results were reported for lentils with hardness ranging from 48.1, 47.1 to 50.0 N. Therefore, the use of enzymatic modifications would contribute to improved pasta quality characteristics